ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT JAPFA COMFEED INDONESIA TBK PERIODE 2021-2023 - Setianingsih, Ria; Hidayah, Nurul; Najib, Muhammad Thoha Ainun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Financial statements prepared by companies have an important role as a decision-making tool both internally and externally. Cash flow statements make an important contribution to financial statement users in interpreting the relationship between net profit and cash flow. In addition, the information presented in the cash flow statement is more accurate in reflecting the company's actual cash. Japfa Comfeed Indonesia Tbk, one of the companies that will be explained, is the largest and integrated company operating in the agri-food sector in Indonesia. The company's main business units are making animal feed, breeding chickens, processing poultry, and cultivating agriculture. This study uses quantitative data, data presented in the form of numbers. The results of this study show that the company's financial condition is not good. Because PT. Japfa Tbk